RARE CASE OF ESOPHAGUS LESION IN PATTENT WITH BEHCET’S DISEASE - V. G. Barskova; Z. S. AIkeberova; S. G. Radenska-Lopovok; S N Skridlevsky (Научно-практическая ревматология, 2001)
33-year-old patient with Behcet's disease developed severe lesion of gastro-intestmal tract involving esophagus. Behcet’s disease diagnosis was verified by recurrent aphtous stomatitis, genital ulcers and erythema nodosum. Peculiarity of this case was wide involving of gastro-iniestinal tract with multiple ulcers in ileocecum and esophagitis leading to the development of diverticulum and gullet narrowing. This case demonstrates the results of late diagnosis of the disease as the diagnosis was determined in IS years after the onset of first symptoms.